Peer Support Intervention’s Impact on Glycemic Control Among Type 2 Diabetes Mellitus Patients - Dita Hanna Febriani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Several models have been developed to provide support for patient self-management to control their blood glucose. Peer support intervention believed to bring positive impact on glycemic control in patient with type 2 diabetes mellitus. The aim of this review was to identify the effect of several peer support interventions on glycemic control among adult with type 2 diabetes mellitus. An integrative search was conducted in electronic databased Pub Med, CINALH, and Cochrane. The inclusion criteria of studies included were employed peer support intervention, randomized control trial in patient with type 2 diabetes mellitus, glycemic control as outcome, English language, published in last 10 years, and available in free full text. Seven studies met the inclusion criteria and included in the further analysis. Five studies reported peer support intervention found statistically significant to improve glycemic control through decreasing HbA1c level. Short term peer support intervention provide potential benefit on glycemic control.